Corrigendum: Characterizing the role of monocytes in T cell cancer immunotherapy using a 3D microfluidic model [Front Immunol, 9, (2018), (416)] DOI: 10.3389/fimmu.2018.00416 - Lee S.W.L. (John Wiley and Sons Inc., 2019)
10.3389/fimmu.2018.01719